Toxicity of Photobacterium damselae subsp. damselae strains isolated from new cultured marine fish - Labella Vera, Alejandro Manuel; Sanchez-Montes, Nuria; Berbel, Concepción; Aparicio, Manuel; Castro, Dolores; Manchado, Manuel; Borrego, Juan José (Inter-Research, 2010)
The in vivo and in vitro toxicity of bacterial cells and their extracellular products (ECPs) from 16 strains of Photobacterium damselae subsp. damselae isolated from 7 epizootic outbreaks were evaluated. On the basis of their 50% lethal dose (LD50) values (about 1 × 105 CFU), these strains may be considered as moderately virulent. However, their ECPs were strongly lethal for redbanded seabream Pagrus auriga causing fish death within 2 h post-inoculation (protein concentration ranged between 2.1 and 6.41 μg g–1 fish). The bacterial ECPs tested exhibited several enzymatic activities, such as amylase, lipase, phospholipase, alkaline phosphatase, esterase-lipase, acid phosphatase, and β-glucosaminidase. These ECPs displayed a strong cytotoxic effect on 4 fish and 2 mammalian cell lines, although this activity disappeared when ECPs were heated at 100°C. The virulence of the strains tested could not be related to the hemolytic activity or to the production of the toxin damselysin. Therefore, another unknown type of toxin could play an important role in the virulence mechanisms of this bacterial pathogen.
Keywords: Peces - Enfermedades; Toxicity; ECP; Photobacterium damselae subsp. damselae; Cultured marine fish